Brazilian academic economics: A picture from the ANPEC exam microdata - Francis C. Petterini (EconomiA, 2020)
The ANPEC exam has been an important instrument for the Brazilian academic economics since the 1970s. Nowadays, practically all graduate program in economics uses it as selection mechanism. This research has tabulated its microdata to produce a picture of what these numbers can reveal about recent past. The main highlights are: master courses demand and supply are numerically closer; students' profiles are not changing, mostly they are white men; many candidates seems to answer at random; outcomes in EB test are little correlated with other results; an applicant needs to correctly answer at least three questions (out of 15) in each test to be selected in most programs; many well-ranked students are not selected anywhere; candidates tend to stay in their home states; and, applicants' motivations and expectations are ambiguous.
Keywords: A23; C29; I23; R53; 330; Academic economics; ANPEC exam; Microdata analyses